2020
DOI: 10.1109/access.2020.3008165
|View full text |Cite
|
Sign up to set email alerts
|

Using EEG and Deep Learning to Predict Motion Sickness Under Wearing a Virtual Reality Device

Abstract: Virtual Reality (VR) research has been widely applied in many fields. VR promises to deliver the experience that is beyond the user's imagination. One of the advantages of VR is the feeling it gives of being there. VR can provide experiences impossible in the real world, such as flying, diving in deep water, exploring outer space, or living with dinosaurs. Despite the improvements in the software and hardware, the problem of motion sickness remains. We implement a deep learning model to train and predict motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 48 publications
1
62
0
3
Order By: Relevance
“…The final list of four papers [26][27][28][29] included in this review were closely scrutinized and encoded to capture a variety of attributes in relation to experimental procedures, data preprocessing steps, and DL architecture choices. Table 1 provides a detailed summary of these papers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final list of four papers [26][27][28][29] included in this review were closely scrutinized and encoded to capture a variety of attributes in relation to experimental procedures, data preprocessing steps, and DL architecture choices. Table 1 provides a detailed summary of these papers.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, one paper was a review paper reporting no empirical data. This screening resulted in a final list of four papers that meet the eligibility criteria [26][27][28][29]. Therefore, the current review focused on these four papers.…”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Saghafian et al also suggested the need to measure realism with emotions within a stressful VR experience [ 38 ]. Motion sickness, disorientation and discomfort are also potential stressors when experiencing the VR [ 47 , 59 ]. Measuring these aspects of the VR using questionnaires has the limitation of inaccuracy as the user experiences are reported after the VR session [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motion sickness, disorientation and discomfort are also potential stressors when experiencing the VR [ 47 , 59 ]. Measuring these aspects of the VR using questionnaires has the limitation of inaccuracy as the user experiences are reported after the VR session [ 59 ]. Using the EEG signals, Liao et al developed a prediction model to detect motion sickness in VR.…”
Section: Discussionmentioning
confidence: 99%